Navigating a Climate in Crisis through a Biomimetic Epistemology - Elizabeth McCormick; David Thaddeus (Enquiry: The ARCC Journal of Architectural Research)
We have entered a geological epoch where environmental change is driven primarily by human activity. The technology-centric approach to sustainable development as the dominant model of innovation in industrialized countries has led to expansive ecological degradation. This paper critiques this paradigm and builds on existing literature from environmental philosophy to propose a new model of ethical, bio-inspired architectural thinking. Though Biomimicry is often celebrated as a model for nature-inspired innovation, it can inadvertently reinforce notions of mastery over nature, a harmful phenomenon that environmental philosopher Freya Mathews calls ‘anthropocentric triumphalism.’